Pregnant African American Women's Perceptions of Neighborhood, Racial Discrimination, and Psychological Distress as Influences on Birth Outcomes. Issue 1 (January 2020) - Dove-Medows, Emily; Deriemacker, Amanda; Dailey, Rhonda; Nolan, Timiya S.; Walker, Deborah S.; Misra, Dawn P.; Kavanaugh, Karen; Giurgescu, Carmen
Abstract: Background: African American women are more likely to experience preterm birth compared with White women. Social factors such as neighborhood disorder and experiences of racial discrimination, which disproportionately affect African American women, may partially explain these disparities. Purpose: The purpose of this study was to examine pregnant African American women's perceptions of neighborhood disorder, racial discrimination, and psychological distress and whether these concepts were viewed as influences on birth outcomes. Study Design and Methods: Using a mixed-methods approach, seven pregnant African American women completed questionnaires including scales for neighborhood disorder (Ross Neighborhood Disorder Scale), racial discrimination (Experiences of Discrimination), and psychological distress (Center for Epidemiological Studies Depression Scale; Psychological General Well-Being Index). All constructs were also assessed by semistructured interviews. Within- and across-case analyses were conducted to compare agreement and discordance between the data sources for each construct and to note patterns in the data. Results: The qualitative interviews provided data about women's experiences that were not captured by questionnaires alone. All of the women disclosed concerns about neighborhood conditions, experiences of discrimination, and psychological distress either reported on the questionnaires, during the qualitative interviews, or both. The mixed-methods approach provided a rich source of data that brought into focus the depth of the perceptions around these constructs. Clinical Implications: Maternal–child nurses should assess perceptions of neighborhood environment, racial discrimination, and psychological distress, as these factors may increase the risk for adverse pregnancy and birth outcomes. Abstract : African American women are more likely to experience preterm birth compared with White women. Social factors such as neighborhood disorder and experiences of racial discrimination, which disproportionately affect African American women, may partially explain these disparities. In this study pregnant African American women were interviewed to get their perceptions of neighborhood disorder, racial discrimination, and psychological distress and whether these concepts were viewed as influences on birth outcomes.